LABORATORY MODEL LANDSLIDE MONITORING SYSTEM USING INTERNET OF THINGS (IOT) TECHNOLOGY - Manuhutu, Fredrik; Souisa, Matheus; Sapulete, Sisca M. (Indonesian Physical Review, 2025)
A landslide disaster is one of the natural disasters that has a detrimental impact on society. This impact can be avoided if the community knows the signs of landslides and gets a warning that a landslide will occur. Therefore, this study aims to design an laboratory landslide warning monitoring system based on Internet of Things (IoT) technology. Landslide monitoring using a tilt sensor connected to a web communication network. Before data testing, IoT sensor calibration was carried out. The calibration results showed a coefficient of determination (R2 = 0.9967), so that this sensor system can be used as a smart sensor in monitoring landslides. In the data acquisition process, the IoT system sends data in real time which is received by the computer via the internet network. The web communication network displays the results in the form of a 2D profile in real time, namely a graph of the slope angle against time. To confirm the web monitoring data, a computer programming language is used to display a 3D profile of the slip plane. The study results show that IoT technology can monitor landslides and the presence of artificial rain in real time with a reading of the soil displacement sensor of 32.4Â°. At this angle, a landslide occurs until it deposits under the foot of the slope, with a landslide mass deposition rate of 0.0012 m3/s. The designed IoT system is portable and permanent and can monitor landslides. This system can be developed more widely in areas prone to landslides for smart communities and can be used as a disaster prevention and mitigation movement in arranging spatial planning based on disaster mitigation. This research can advance our understanding of landslide monitoring dynamics using web-based IoT systems, providing important insights for mitigation strategies and future research.